Cutting the network? Facebook's Libra currency as a problem of organisation - Daniel Tischer (Finance and Society, 2020)
This essay explores the organisational character of Facebook's Libra currency by undertaking a critical reading of documents published by the Libra Association. Drawing on the conceptual work of Marilyn Strathern and Michel Serres, it illustrates how ownership cuts the network and encourages parasitism as a means of driving future profit. Central to this is the claim that Libra is not an exercise in democratising money, but rather, the opposite: Libra is run as a club, for the benefit of club members. The conceptual theme of "cutting" is used to organise the argument. Rather than a cutting-edge technology, Libra's true innovation is organisational and consists in overturning the decentralised character of blockchain, such that distributed ledger technology is re-centralised by big tech firms. Outsiders are thus cut-off from Libra; only those inside the club have the right to participate in Libra and its governance. This position also affords members an exclusive capacity to take a cut of the profits generated through Libra. As a private organisation, members have sole rights to future profits generated from the Libra ecosystem and are in this way incentivised to create new product opportunities over time.
Keywords: 300; Facebook; Libra; digital payments; cryptocurrencies; organisation; club; network